Experimental Study on Physical and Rheological Properties of Trinidad Lake Asphalt Modified Binder - Krzysztof Kołodziej; Lesław Bichajło; Tomasz Siwowski (Applied Sciences, 2021)
Mastic asphalt (MA) has been recognized as one of the most deformation-resistant and thus durable materials for bridge pavement. The performance properties of MA are highly dependent on the physical and rheological properties of the binder applied in the MA mixture. To modify the binder properties to obtain the expected performance of the MA mixture, Trinidad Lake Asphalt (TLA) is often applied. In this study, the TLA-modified binders to be used in mastic asphalt bridge pavement systems were evaluated to develop the optimum material combination using conventional and performance-related testing. Physical and rheological tests were carried out on TLA-modified binders with the different modifier content in the range of 10–50% on a weight basis. The tests revealed that the TLA modifier addition to the 35/50 base bitumen should be close to the value of 20%. Higher concentrations of TLA may make the binder very stiff and could induce low-temperature cracks in mastic asphalt.